PRAKTIK HUTANG PIUTANG BERSYARAT DALAM PERSPEKTIF HUKUM ISLAM: STUDI KASUS DI DESA PASIR KECAMATAN AYAH KABUPATEN KEBUMEN - Miftahur Miftah; Ani Muktiroh (Fakultas Ekonomi dan Bisnis Islam, 2025)
This study examines the practice of conditional debt agreements among fishermen in Pasir Village, Ayah District, Kebumen Regency, and analyzes it from the perspective of Islamic law. In this community, fishermen who require capital for fishing operations typically borrow funds from private lenders. However, the lending agreement includes a mandatory condition: fishermen must sell their entire catch to the lender at a price determined by the lender, which is significantly lower than the market price at the local fish auction. This practice creates a dependency cycle that economically disadvantages the fishermen. This research employs a qualitative field approach, using interviews, observation, and documentation, combined with a normative juridical analysis to assess compliance with principles of Islamic jurisprudence (fiqh muamalah). Data were analyzed deductively by comparing empirical facts with Islamic legal sources and scholarly views. The findings reveal that although the practice begins as a financial assistance mechanism, it gradually transforms into an exploitative economic transaction driven by profit-seeking motives from the lender. Such conditional benefit requirements violate the core principle of qardh, which is intended as a benevolent contract (tabarru’), and fall under the category of riba prohibited in Islamic law. Therefore, the conditional debt practice observed in Pasir Village is deemed invalid according to Islamic jurisprudence.